2016
DOI: 10.1021/acs.inorgchem.5b02543
|View full text |Cite
|
Sign up to set email alerts
|

Scrutinizing the Noninnocence of Quinone Ligands in Ruthenium Complexes: Insights from Structural, Electronic, Energy, and Effective Oxidation State Analyses

Abstract: The most relevant manifestations of ligand noninnocence of quinone and bipyridine derivatives are thoroughly scrutinized and discussed through an extensive and systematic set of octahedral ruthenium complexes, [(en)2RuL](z), in four oxidation states (z = +3, +2, +1, and 0). The characteristic structural deformation of ligands upon coordination/noninnocence is put into context with the underlying electronic structure of the complexes and its change upon reduction. In addition, by means of decomposing the corres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 139 publications
(200 reference statements)
8
25
0
Order By: Relevance
“…Within each family, the forms of DFT exchange and DFT correlation remain constant, allowing the effect of EXX on the properties under study to be estimated. Results for PBE (GGA functional, EXX=0%), 89 PBE0 (hybrid-GGA functional, EXX=25%), 90 TPSS (meta-GGA functional, EXX=0%), 91 TPSSh (hybrid-meta-GGA functional, EXX=10%) 92 and M11 (RSH functional, 42.8/100% of EXX at short/long range) 93 are in accordance to their EXX contribution compared to the results of the 11 functionals (see SI).…”
Section: Methodssupporting
confidence: 62%
See 1 more Smart Citation
“…Within each family, the forms of DFT exchange and DFT correlation remain constant, allowing the effect of EXX on the properties under study to be estimated. Results for PBE (GGA functional, EXX=0%), 89 PBE0 (hybrid-GGA functional, EXX=25%), 90 TPSS (meta-GGA functional, EXX=0%), 91 TPSSh (hybrid-meta-GGA functional, EXX=10%) 92 and M11 (RSH functional, 42.8/100% of EXX at short/long range) 93 are in accordance to their EXX contribution compared to the results of the 11 functionals (see SI).…”
Section: Methodssupporting
confidence: 62%
“…Indeed, based on the X-ray structure of neutral bpy 0 , 34 monoanionic bpy -1 35 and dianionic bpy -2 , 35,36 it has been shown that the intramolecular CC and CN bond lengths of the bpy ligand vary as a function of the overall ligand charge because of changes in the bonding and antibonding interactions of the bpy 0 p* orbital (lowest unoccupied molecular orbital, LUMO). 35 This structural signature, which has also been studied in other non-innocent ligands such as substituted bipyridine, [37][38][39] phenanthroline, 40 terpyridine, 38,39,41 pyridine-2,6-diimine 40 or quinones 42 is a good indicator of both the electronic population of the coordinated ligands and the electronic structure of the complexes. [43][44][45][46][47] If high resolution X-ray crystallographic structures can be obtained, accurate bond lengths and the way in which they change upon varying the oxidation level can allow the redox state of the ligands in their coordination complexes to be determined unambiguously.…”
Section: Introductionmentioning
confidence: 99%
“…[4] Generally, complexes with transition metals in the 5th and 6th row undergo reactions such as oxidative addition and reductive elimination in which the oxidation state changes by two units, while complexes with 4th row metals frequently show one-electron redox chemistry. [6] Without such ligands, mononuclear Ru I complexes are inherently unstable. Ruthenium complexes with redox active ligands have been reported to undergo one-electron reductions/oxidations, but these occur at the ligand while the oxidation state at the metal center remains + 2.…”
mentioning
confidence: 99%
“…Ruthenium complexes with redox active ligands have been reported to undergo one-electron reductions/oxidations, but these occur at the ligand while the oxidation state at the metal center remains + 2. [6] Without such ligands, mononuclear Ru I complexes are inherently unstable. [7] For this reason, most of the Ru I species are reactive intermediates detected in situ, [7,8] or form binuclear/ multinuclear complexes containing metal-metal bonds.…”
mentioning
confidence: 99%
See 1 more Smart Citation